Philadelphia Communists, 1936-1956 - Lyons, Paul (Temple University Press, 1982)
In Philadelphia Communists, 1936-1956, Paul Lyons constructs a model of the Philadelphia Party experience. He focuses on the experience of becoming, being, and remaining a radical in a particular local setting. Lyons interviewed 36 "Old Leftist" Party members from the Depression generation, focusing on family background, the process of radicalization, organizing experiences, the significance of marriage and family, the role of ethnicity, the influence of the local Party subculture and social network, post-Party experiences and perspective. Lyons then uses these interviews to describe the Party subculture at a specific temporal and geographic location.